Perspektif Akad Muzaraah dalam Perspektif Fiqh Muamalah - Muhamad Azfa Matin; Ali Usman Harahap; Muhamad Aulia Rahman (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study re-examines the concept and practice of the muzara‘ah contract within the framework of fiqh muamalah, combining an analysis of classical literature with the dynamics of modern agriculture. Muzara‘ah, as a model of collaborative land management, plays a strategic role in the economy of agrarian communities. However, its implementation raises debates regarding yield uncertainty, risk-sharing, and differing scholarly opinions. Using a literature review approach, this study analyzes authoritative references such as al-Mabsut, al-Mughni, and Bidayat al-Mujtahid, along with scientific journal articles on contemporary agricultural profit-sharing models. The findings indicate that scholars (fuqaha) generally permit muzara‘ah contracts, provided that profit-sharing ratios are clearly determined and the rights and obligations of all parties are fairly regulated. In the modern era, challenges such as environmental instability, technological changes, and agrarian policies require enhancements in contract mechanisms through clearer agreements, effective risk management, and adaptation to the needs of the agricultural industry. This study emphasizes the importance of adjusting fiqh muamalah to maintain relevance for contemporary agricultural practices.